Individual, sociodemographic and institutional variables associated with the retention of first year students of the Programa Académico de Bachillerato of the University of Chile - Munizaga Mellado, Felipe René; Rojas-Murphy Tagle, Andrés Felipe; Leal De Calisto, Rodrigo Andrés (Education Policy Analysis Archives, 2019)
Retention in Higher Education (HE) in Latin America and the Caribbean (LAC) has considerable social, economic and individual effects (Project ALFA-GUIA, 2013, CINDA, 2006). Retention has assumed technical relevance in studies of quality in education, at the same time that it increases its importance in international rankings and in the accreditation processes of university institutions. According to a World Bank study (Ferreyra et al., 2017) HE in the region is characterized by: 1) an average completion rate of 46%, with important differences between one country and another; 2) the existence of an exponential increase in enrollment, doubling its regular rate; 3) the incorporation of “new students”, previously underrepresented in the HE. Taking into account that in the region there is a lack of predictive research on the phenomenon of retention (Munizaga, Cifuentes & Beltrán, 2018), this study aims to review recent information regarding retention in LAC, in order to reach an agreed definition about the phenomenon, with the intention of broadening the discussion on how to guarantee the retention of students in a context of equitable and inclusive HE (Espinoza, González & Latorre, 2009). All in all, this work seeks to answer what are the individual, sociodemographic and institutional variables associated with the retention of first-year students of the Programa Académico de Bachillerato of the University of Chile? Through a binary logistic regression model, composed of eight variables, the following six significant variables were identified: ethnic origin of the students, approval of all credits and gratuity, with a positive relationship with retention. On the other hand, the preference, gender and score of the university selection test, reach a negative association with retention. The main recommendations of this study are, at the institutional level, to offer broader academic trajectories and, at the state level, to assume responsibilities regarding the financing of students.